(untitled) (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Introduction Takayasu arteritis (TKA) is a rare large vessel vasculitis, most prevalent in Asia and affecting females ages 10-40 years. Through unclear etiology, it triggers chronic granulomatous inflammation leading to vessel wall thickening, stenosis, and occlusion. Manifestations vary from mild malaise to severe ischemic complications. Diagnosis hinges on clinical criteria, including angiography, and exclusion of mimicking conditions like giant cell arteritis, fibromuscular dysplasia, or atherosclerosis. Treatment necessitates immunosuppression and anti-inflammatories to curb disease progression and limit complications. Case Presentation A 61-year-old Caucasian female presented with claudication of the upper extremities upon using the shower. She reported episodes of headache, myalgia, fever and chills of several months. She reported fatigue with overhead reaching and difficulty finding her pulse on her upper extremities. Labs were notable for elevated ESR and CRP. MRA chest showed smoky thickened appearance of the descending aorta wall, some missing wall thickening in origins of the left common carotid and left subclavian arteries. PET scan revealed diffuse hypermetabolic activity involving the bilateral common carotid arteries, peripheral aortic arch and descending thoracic aorta (Figure 1). With these ongoing symptoms and characteristic features on imaging, we established the diagnosis of TKA. She was started on 5mg oral prednisone daily and methotrexate 10mg weekly with daily folic acid. Conclusion This case highlights the diagnosis and treatment of a rare condition, Takayasu arteritis, the pulseless disease. TKA is a challenging condition to study and understand fully, but advancements in medical knowledge, imaging, and management are gradually improving our understanding and ability to diagnose and treat this condition. With increased awareness of this condition, earlier detection and monitoring will serve to benefit future patient populations.